The Implementation of Protocol-Based Utilization of Neuromuscular Blocking Agent Using Clinical Variables in Acute Respiratory Distress Syndrome Patients. (19th March 2021) - Hadique, Sarah; Badami, Varun; Forte, Michael; Kovacic, Nicole; Umer, Amna; Shigle, Amanda; Gardo, Jordan; Sangani, Rahul
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The recent conflicting data on the mortality benefit of neuromuscular blocking agents in acute respiratory distress syndrome and the potential adverse effects of continuous neuromuscular blocking agent necessitates that these medications should be used judiciously with dose reduction in mind. The aims of the study were to improve the process of care by provider education of neuromuscular blocking agent titration and monitoring and to determine the impact of clinical endpoint based neuromuscular blocking agent titration protocol. Design: We conducted a proof-of-concept historically controlled study of protocol-based intervention standardizing paralytic monitoring and titration using clinical variables. Education of the protocol was provided to ICU staff via bedside teaching and workshops. The primary outcomes were the time to reach goal paralysis and cumulative neuromuscular blocking agent dose. Secondary outcomes included maintenance of deeper sedation (Richmond Agitation and Sedation Scale –5) prior to neuromuscular blocking agent initiation, total time on mechanical ventilation, length of stay, and mortality. Setting: Medical ICU at a quaternary academic hospital between March 2019 and June 2020. Patients: Adult severe acute respiratory distress syndrome (Pao 2 /Fio 2 <150) patients requiring neuromuscular blocking agent for greater than or equal to 12 hours. Eighty-two patients fulfilled inclusion criteria, 46 in the control group and 36 in the intervention group. Interventions: Education and implementation of standardized protocol. Measurements and Main Results: Compared with the control group, the time to reach goal paralysis in the intervention group was shorter (8.55 ± 9.4 vs 2.63 ± 5.9 hr; p < 0.0001) on significantly lower dose of cisatracurium (total dose 1, 897.96 ± 1, 241.0 vs 562.72 ± 546.7 mg; p < 0.0001 and the rate 5.84 ± 2.66 vs 1.99 ± 0.95 µg/kg/min; p < 0.0001). Deeper sedation was achieved at the time of initiation of neuromuscular blocking agent in the intervention arm (mean Richmond Agitation and Sedation Scale –3.3 ± 1.9 vs –4.3 ± 1.7; p = 0.015). There was no significant difference in total time on mechanical ventilation, length of ICU stay, length of hospital stay, and mortality between the two groups. Conclusions: Implementation of comprehensive education, standardization of sedation prior to neuromuscular blocking agent initiation, integration of clinical variables in determining paralysis achievement, and proper use of peripheral nerve stimulation served as optimal strategies for the titration and monitoring of neuromuscular blocking agent in acute respiratory distress syndrome. This reduced drug utilization while continuing to achieve benefit without causing adverse effects.